Brand against the machine how to build your brand, cut through the marketing noise, and stand out from the competition - Morgan, John 1961- (John Wiley & Sons, 2012)
Ditch traditional corporate branding to create a powerful, recognizable brand Brand Against the Machine offers proven and actionable steps for companies and entrepreneurs to increase their brand visibility and credibility, and to create an indispensable brand that consumers can relate to, thus becoming life-long customers. Discover the aspirational currency that makes your brand one that people want to be or want to be friends with. Learn how to be real with your audience and make strategic associations to establish credibility. Brand Against the Machine will help you stand out, get noticed, a.